Stability of the K-12 Program in Philippine Education - Ansibey , Susan (Journal of Interdisciplinary Perspectives, 2024)
This meta-analysis study examined articles written by various researchers that investigate the K–12 program in Philippine schools from the perspective of different stakeholders. The study aimed to assess the stability of the K–12 program in Philippine education based on the perceptions and experiences of students, teachers, parents, and other stakeholders. A systematic and logical approach was employed, considering both the inclusion and exclusion of relevant data to understand the challenges and potential improvements of the program. The findings reveal both positive and negative aspects of the programs’ stability, providing valuable insights for future research and recommendations. Most respondents’ experiences were viewed positively, indicating a considerable level of stability in the K–12 program. However, there were also negative experiences reported, suggesting areas where the program needs improvement. The study serves as a valuable reference for understanding the stability of the K–12 program in Philippine education and provides actionable recommendations to improve the quality of education.